ANALYSIS OF THERMAL AND AERODYNAMICS PERFORMANCE OF BATAK TOBA TRADITIONAL HOUSE BY IMPLEMENTING DIGITAL SIMULATION AND FIELD MEASUREMENT - Yuri Hermawan Prasetyo (Pusbindiklat - LIPI, 2016)
Traditional house is believed to have a better thermal performance compared to the modern house. Utilization of passive design in buildings can refer to the passive system used in a traditional house through natural ventilation and local materials application. Digital simulation was used to evaluate the thermal performance of the Batak Toba Traditional House by comparing field measurement data; and as a validation tool. This study aims to determine the thermal and aerodynamic performance of Batak Toba Traditional House by using digital simulation and field measurements. The used method was by comparing the results of digital simulation analysis with indoor and outdoor direct temperature measurements of the Batak Toba Traditional House. The softwares used for simulation were Meteonorm, Ecotect and CFD-ACE+. The measurements were conducted for 24 hours in May 4th-5th and April 26th-27th 2013 within one hour time interval. The results of the analysis of digital simulation show the same phenomenon compared with the result of field measurement that is 80% in range thermal comfort within one year. Field measurement results showed that the thermal conditions resulted from all day field measurement was under the upper limit temperature reference of thermal comfort with natural ventilation, that is 29 °C.